Akhlak Dan Etika Peserta Didik Berbasis Pendekatan Normatif Ditinjau Dari Perspektif Al-Qur’an Dan Hadits - Tsania Tazlila Wardani; Shifa Azzahra; Chadiza Azzahra Lubis; Sri Mulyani; Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Morals and ethics are something that is very important to be developed in students. The poor morals and ethics of students towards teachers, colleagues, underclassmen and others are proof that education in the country has not fully succeeded in shaping the character of good students. For this reason, special and intensive coaching is needed on moral and ethical development based on a normative approach that is integrated with the Qur'an and Hadith. The purpose of this study is to examine the morals of students towards teachers according to the Qur'an and Hadith and how to overcome the problem of bad moral decadence in students. This research method is qualitative descriptive. The approach used is the library method, the materials collected are books, magazines and journal articles related to this research theme from previous research works. The data sources include verses of the Quran and Hadith that contain the morals of students towards teachers and the views of experts contained in related articles. The results of this study show that; (1) special and intensive coaching is needed on students' morals and ethics while in school, (2) Improve students' Islamic studies, (3) Tell the morals of noble prophets and ompanions, (4) Improve the quality and quantity of worship, (5) Provide good examples and examples.